2006
DOI: 10.1111/j.1944-9720.2006.tb02263.x
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Incidental Vocabulary Acquisition in Relation to Learner Proficiency Level and Word Frequency

Abstract: This study examined the relationship between learners' incidental vocabulary acquisition and their level of proficiency, and between acquisition and word frequency in a text. Participants were Turkish learners of English at three proficiency levels. One reading text and four vocabulary tests were administered over a two‐week period. Analyses of the data revealed that lexical gains from reading were significant for each group (p < .05). The higher proficiency groups were able to acquire more words than lower le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 29 publications
6
51
1
Order By: Relevance
“…The findings also indicate that the more exposed to formulaic expressions the students were through their textbook, the more frequently they used them in the oral proficiency exam, a finding in line with the literature (e.g., Ellis, Simpson-Vilach & Maynard, 2008;Tekmen & Daloglu, 2006;Webb, Newton & Chang, 2013). For instance, Ellis, Simpson-Vilach and Maynard (2008) state that learners are likely to know the words which they encounter more than the others.…”
Section: The Use Of Formulaic Language In Oral Proficiency Examssupporting
confidence: 74%
“…The findings also indicate that the more exposed to formulaic expressions the students were through their textbook, the more frequently they used them in the oral proficiency exam, a finding in line with the literature (e.g., Ellis, Simpson-Vilach & Maynard, 2008;Tekmen & Daloglu, 2006;Webb, Newton & Chang, 2013). For instance, Ellis, Simpson-Vilach and Maynard (2008) state that learners are likely to know the words which they encounter more than the others.…”
Section: The Use Of Formulaic Language In Oral Proficiency Examssupporting
confidence: 74%
“…The authors suggested that there was a 50% chance of correctly identifying word form in the post-test three months later if learners met the word eight times or more. Tekmen and Daloglu (2006) examined the predicting power of word frequency in a text over word learning. Three groups of Turkish learners of English participated in the reading of an authentic text(The Golden Fleece) with about 2,400 words and four lexical tests administered over a two-week period.…”
Section: Iva and Word Exposure Frequency: A Controversial Issuementioning
confidence: 99%
“…This was not surprising because incidental word learning was contingent on a number of variables. Three of these were participants' word level (Tekmen & Daloglu, 2006), context that a word is in (Webb, 2008), and part of speech (Zimmerman, 2009). As stated by Chen and Truscott (2010), "The goal of research should not be to identify a definitive number of exposures needed but rather to understand a complex process involving multiple, interacting variables" (p. 694).…”
Section: Literature Review Incidental Vocabulary Learningmentioning
confidence: 99%